Struktur Klausa Bahasa Dayak Tagol - Buha Aritonang (Metalingua: Jurnal Penelitian Bahasa, 2017)
The problem of this research is the structure of the clause Dayak Tagol the languange which spoken by people in Tau Lumbis Village, Subdistrict Lumbis Ogong, Nunukan Regency, North Kalimantan Province. This research aim to describe a general overview of the life Dayak Tagol people and the structure of the clause the languange of Dayak Tagol.  This research used a qualitative research method. The results of this research shows that the structure of the clause Dayak Tagol can be classified into (1) the structure of the clause predicated of non-verb and (2) the structure of the clause predicated of verb. The structure of the clause predicated of non-verbal can be intangible (1) clause predicate nominal, (2) clause adjectival, (3) numeralia, and (4) clause the phrase prepositional. Based on the research data, the structure of the clause verbal consists of (1) clause intransitive, (2) clause ekatransitif (the clause argued the core two), and (3) clause be dwitransitive (the clause argued the core three)